STUDY ON ELDERLY PEOPLE AS RESOURCE IN SOCIETY AND FAMILY - SABĂU, Gheorghe; ACQUI, Eva (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2023)
In this paper, our interest has been that of identifying the possibilities of using elderly people as human resource in family and society, taking into account the present trend of doing away with the dependence state of elderly people, providing solutions to identify some active social roles that keep them active, values promoted by the theory of activity. Looking through the literature in the field, we have observed that it does not offer too many data on the social and cultural needs of retirees, on their spending free time, data which should help us find solutions to increase the quality of life. We have attempted and to a greater extent we have succeeded in promoting activities that can lead to “more active ageing”, so that these people remain active on the community and territorial level as long as possible. REZUMAT. Studiu privind persoanele vârstnice ca resursă în societate și în familie. În această lucrare, interesul nostru a fost de a identifica posibilitățile de utilizare a persoanelor vârstnice ca resursă umană în familie și în societate, luând în considerare tendința actuală de înlăturare a stării de dependență a persoanelor vârstnice, oferind soluții pentru a identifica unele roluri sociale active, care să-i mențină în activitate, valori promovate de teoria activității. Căutând în bibliografia de specialitate, am observat că aceasta nu ne oferă prea multe date despre nevoile sociale și culturale ale pensionarilor, despre petrecerea timpului liber al acestora, date care să ne ajute în a găsi soluții pentru creșterea calității vieții. Am încercat și în mare măsură am reușit să promovăm activități care să ducă la o „îmbătrânire cât mai activă”, astfel încât aceste persoane la nivel comunitar și teritorial să rămână active cât mai mult timp. Cuvinte cheie: pensionari, familie, activitate, societate Received 2022 October 18; Revised 2022 November 21; Accepted 2023 November 22; Available online 2023 May 30; Available print 2023 June 30.